Unraveling the Internationalization Barriers among Oil and Gas SMEs: A Path to Global Expansion - Janiffa Saidon; Amir Afiq Mohd Yusof; Nurul Ainun Ahmad Atory; Faizah Mashahadi; Mohd Zulkifli Abdullah; Hairulnizam Hashim; Siti Nor Bayaah Ahmad (AMH International, 2023)
The remarkable expansion of globalization stands as one of the most significant phenomena in the twenty-first century, shaping both the business landscape and robust strategic approaches that prioritize the internationalization of domestic firms. In addition to large multinational corporations, small and mediumsized enterprises (SMEs) also recognize the vast opportunities international markets offer for business growth and development. Furthermore, SMEs that venture into global markets can strengthen their competitiveness and global presence by integrating valuable global experiences and incorporating their benefits into their domestic operations. Despite the potential, SMEs' involvement in the global market has remained disappointingly low, with little improvement since 2011. In light of this challenge, our study endeavors to unravel the multifaceted factors contributing to SMEs' internationalization dilemmas. Analyzing a total of 409 valid datasets, the findings highlighted the main factor behind SMEs' hesitancy to engage in internationalization: a lack of resources. Consequently, it becomes crucial for SMEs, particularly those in the Oil and Gas Equipment and Service segments, to focus on strengthening their resources to facilitate the internationalization process. Complementing this resource-centric approach, adjustments in managers' attitudes are equally crucial, as they have the potential to ignite SMEs' active engagement in international markets, ultimately contributing to national economic growth.